Assessment of skin permeability to topically applied drugs by skin impedance and admittance. (1st November 2017) - Schwingenschuh, Simon; Scharfetter, Hermann; Martinsen, Ørjan G; Boulgaropoulos, Beate; Augustin, Thomas; Tiffner, Katrin I; Dragatin, Christian; Raml, Reingard; Hoefferer, Christian; Prandl, Eva-Christina; Sinner, Frank; Hajnsek, Martin
Abstract: Objective : Pharmacokinetic and pharmacodynamic studies of topically applied drugs are commonly performed by sampling of interstitial fluid with dermal open flow microperfusion and subsequent analysis of the samples. However, the reliability of results from the measured concentration-time profile of the penetrating drug suffers from highly variable skin permeability to topically applied drugs that is mainly caused by inter- and intra-subject variations of the stratum corneum. Thus, statistically significant results can only be achieved by performing high numbers of experiments. To reduce the expenditures needed for such high experiment numbers we aimed to assess the correlation between skin permeability and skin impedance/skin admittance. Approach : We performed an ex vivo drug penetration study with human skin, based on the hypothesis that inter-subject variations of the respective concentration-time profiles can be correlated with variations of the passive electrical properties of the skin. Therefore, skin impedance and skin admittance were related to the skin permeability to the model drug Clobetasol-17-proprionate. Main results : The measured low frequency skin impedance and the skin admittance correlated linearly with the drug concentration-time profiles from dermal sampling. Significance : Skin permeability can be assessed by measuring the passive electrical properties of the skin, which enables correction of skin permeability variations. This allows reduction of experiment numbers in future pharmacokinetic and pharmacodynamic studies with human skin ex vivo and in vivo and leads to diminished study costs.